Mobile Money Services Development : The Cases of the Republic of Korea and Uganda - Gutierrez, Eva; Choi, Tony (World Bank, Washington, DC, 2014)
This study intends to increase understanding of how different types of mobile money services have developed in different environments. For this purpose, two countries were selected, the Republic of Korea and Uganda. From these study cases, some conclusions emerge. The development of mobile banking services can appear at different stages of financial sector development, but it requires a vibrant and competitive telecommunications sector. The regulatory environment does not need to be very sophisticated for the mobile industry to emerge. However, some elements appear to be important. The legal framework should allow (or at least not explicitly forbid) nonbank financial institutions to issue money and use banking agents or correspondents. To ensure wider use of the service by the population, it is important to educate the population on the benefits of mobile money services.